Implementasi Kurikulum 2013 Dalam Menanamkan Nilai- Nilai Karakter Pada Mata Pelajaran Akidah Akhlak Di Kelas XI Madrasah Aliyah Swasta Al Wasliyah 68 Pematang Guntung Kabupaten Serdang Bedagai - Kurniawan, Dedi; Barus, Jusua; Yusman; Yusman, Yusman (STAI Tebing Tinggi Deli, 2024)
Learning moral beliefs is very important to pay attention to because learning that is in accordance with the applicable 2013 curriculum will support students in the learning process. Because the 2013 curriculum helps teachers in carrying out learning in accordance with existing rules. The researcher aims to find out the Implementation of the 2013 Curriculum in Instilling Character Values in the Subject of Moral Beliefs in Class XI of Madrasah Aliyah Private Al Washliyah 68 Pematang Guntung, Serdang Bedagai Regency. Researchers pay attention to learning moral faith, because in the moral aqidah lesson there are materials that teach students to form noble character. Madrasah Aliyah Private Al Wasiliyah 68 Pematang Guntung Regency Serdang Bedagai is a school that has Islamic values, so that in Class XI Madrasah Aliyah Private Al Wasiliyah 68 Pematang Guntung Regency Serdang Bedagai. The results of the study show that the Implementation of the 2013 Curriculum in the Ministry of Agriculture.